2013
DOI: 10.1002/pola.26939
|View full text |Cite
|
Sign up to set email alerts
|

BF3·OEt2 in alcoholic media, an efficient initiator in the cationic polymerization of phenyl‐1,3‐benzoxazines

Abstract: 3-Phenyl-3,4-dihydro-2H-1,3-benzoxazine (m 1 ) underwent cationic ring opening polymerization using BF 3 ÁOEt 2 in alcoholic solution under mild conditions. The polymerization of m 1 proceeds through an intermediate hemiaminal ether leading mainly to the formation of polybenzoxazines with diphenylmethane bridges, and not only the classical Mannich-type ones. During the first stages of the reaction, low-molecular weight soluble oligomers containing benzoxazine rings are formed. At longer polymerization times, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Water and IPA in the catalyst were found to have a negative effect. 1 H NMR spectra of the reaction product after 24 h show a decrease in the intensity of the benzoxazine ring methylene signals and the appearance of new signals at 4.4, 4.2 and 3.8 ppm, which can be related with ring opening products [46,47]. According to these results the rest of the study was carried out using Karstedt's catalysts.…”
Section: H Nmr During 24 Hmentioning
confidence: 96%
“…Water and IPA in the catalyst were found to have a negative effect. 1 H NMR spectra of the reaction product after 24 h show a decrease in the intensity of the benzoxazine ring methylene signals and the appearance of new signals at 4.4, 4.2 and 3.8 ppm, which can be related with ring opening products [46,47]. According to these results the rest of the study was carried out using Karstedt's catalysts.…”
Section: H Nmr During 24 Hmentioning
confidence: 96%
“…[76] In peptide chemistry,r eductiono ft he N,O-acetal derivatives of amino acids has been aw ell-known approach to access Nmethylated amino acids.T he methodology also works well to make N-methylated amino alcohols. Table 16 [77][78][79][80][81][82] illustrates some recent examples under different reducing conditions.…”
Section: Reduction Of No-acetalsmentioning
confidence: 99%
“…The methodology also works well to make N‐methylated amino alcohols. Table illustrates some recent examples under different reducing conditions.…”
Section: N‐methylationmentioning
confidence: 99%
“…found that the polymerization of benzoxazine can proceed at room temperature with the assistance of Lewis acids such as PCl 5 , and the polymer with N,O‐acetal‐type structure was formed. Andreu et al . found that under the combined effect of BF 3 ⋅OEt 2 and methanol, the polymerization of benzoxazine can be effectively initiated at 60 °C.…”
Section: Introductionmentioning
confidence: 99%